ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP KEMISKINAN DI KOTA KEDIRI MELALUI PENGANGGURAN SEBAGAI VARIABEL INTERVENING - Hasanah, Amalia Lailatul; Imaningsih, Niniek (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This research aims to find out what factors can influence poverty both directly and indirectly, such as HDI, economic growth and unemployment. The method used in this research is a quantitative method with a multiple linear regression model and an analytical tool in the form of path analysis through the Eviews 12 program. This research uses 15 samples starting from 2007 - 2021 with data sourced from the Kediri City Central Statistics Agency website and East Java. The results of this research show that economic growth and HDI do not have a direct effect on poverty. The specific result is that the direct relationship between economic growth and HDI on poverty is positive and not significant. Meanwhile, for indirect effects, through unemployment on poverty from economic growth and HDI, the results show that only HDI has an indirect effect on poverty through unemployment, while economic growth has no indirect effect on poverty in Kediri City